2021
DOI: 10.1080/14992027.2021.1978567
|View full text |Cite
|
Sign up to set email alerts
|

Speech production in Mandarin-speaking children with cochlear implants: a systematic review

Abstract: Objective: This study aimed to systematically review and critically appraise the literature describing the phonetic characteristics and accuracy of the consonants, vowels and tones produced by Mandarin-speaking children with cochlear implants (CIs). Design: The protocol in this review was designed in conformity with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. EBSCOhost, PubMed, Scopus, PsycINFO, ProQuest Central databases were searched for relevant articles which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…There are existing review papers describing speech perception outcomes in the pediatric Chinese CI population, and prior work has indicated that adult Mandarin-speaking CI patients' ability to recognize and perceive speech is highly impacted by speech rate and noise type. In a multitalker environment, Mandarin-speaking CI users have been shown to be susceptible to interference between concurrent tones (9)(10)(11)(12)(13). However, little is known about how to best advise Chinese-speaking adult CI candidates and to what extent clinicians are consulting the existing complex body of literature.…”
Section: Introductionmentioning
confidence: 99%
“…There are existing review papers describing speech perception outcomes in the pediatric Chinese CI population, and prior work has indicated that adult Mandarin-speaking CI patients' ability to recognize and perceive speech is highly impacted by speech rate and noise type. In a multitalker environment, Mandarin-speaking CI users have been shown to be susceptible to interference between concurrent tones (9)(10)(11)(12)(13). However, little is known about how to best advise Chinese-speaking adult CI candidates and to what extent clinicians are consulting the existing complex body of literature.…”
Section: Introductionmentioning
confidence: 99%